PROPOSAL OF NEW COSMECEUTICAL FORMULATIONS TO BE ELABORATED AT LABIOFAM BUSINESS UNIT, VILLA CLARA - Alonso Arteaga, Daniela; Saucedo Hernández, Yanelis; Alba de Armas, Miguel Ángel; González Bedia, Mirtha Mayra; Gómez Saucedo, Melissa Lliliam; Ruz Sanjuan, Vivian (Centro Azúcar Journal, 2025)
Introduction: Cosmeceuticals are cosmetic products with active biological ingredients that guarantee skin care. The increase in the consumption of cosmeceuticals in Villa Clara, marketed by the Grupo Empresarial Laboratorios Biológicos Farmacéuticos (LABIOFAM) (Pharmaceutical Biological Laboratories Business Group), especially chamomile and honey creams, has led to the optimization of these formulations and their processing technologies in order to guarantee products of higher quality and stability. Objective: To propose two cosmeceutical formulations (chamomile cream and honey cream) with technological quality and physical stability. Materials and Methods: The proposed and elaborated formulations were analyzed from a physical-chemical and technological point of view by means of the following tests: pH, organoleptic properties, analysis of the type of emulsion, bulk density and extensibility. Results and Discussion: Both formulations were direct emulsions and showed adequate organoleptic characteristics, pH, bulk density and extensibility when freshly prepared. The chamomile cream maintained these parameters for six months within the permissible limits. After six months of storage, the honey cream had a pH value slightly lower than the established limit. Conclusions: Both creams complied with the quality control parameters evaluated, with the chamomile cream showing a stability of six months and the honey cream three months.